(untitled) (Bangladesh Renal Journal, 2026)
The study of glomerular disease is a challenging field of nephrology. Glomerular diseases represent a large number of diseases, which are rapidly evolving in number and complexity with the advancement of diagnostic facilities and knowledge of their underlying pathogenic mechanisms. Method : This study looked at 161 kidney biopsy reports from Bangladesh Medical University (BMU) between 2010 and 2025. It included patients aged 16 and older who had biopsies for issues like proteinuria. We collected data about the patients’ clinical details, lab results, and immune system markers. Biopsies were done using automated biopsy guns with ultrasound guidance. After that we processed the tissue with formalin fixation, paraffin embedding, and various microscopy and staining methods. Results: In our study, 49% of patients were male and 51% were female, yielding a male-to-female ratio of 1:1.04,Mesangial proliferative glomerulonephritis (GN) is the most common variety among the primary GN, affecting 26% of patients. MPGN followed as the second most common, at 18%, with an increasing incidence of focal segmental glomerulosclerosis (FSGS) observed in 13% of patients. Among the secondary GN lupus nephritis is most common. Post-infectious GN (PIGN) was seen in 3% of patients, Renal impairment was present in 33 patients, primarily with MPGN and FSGS. Nephrotic-range proteinuria was the most important indication for kidney biopsy, seen in 46% of cases, followed by sub-nephrotic proteinuria with hematuria. Conclusion: The primary aim of the study is to share our experience in clinicopathological and histological spectrum of Glomerulonephritis in Bangladeshi population. Bang. Renal J. 2026; 8(1): 10-15